Evaluation and Management of Respiratory Illness in Children With Cerebral Palsy - Marpole, Rachael; Blackmore, A. Marie; Gibson, Noula; Cooper, Monica S.; Langdon, Katherine; Wilson, Andrew C. (Frontiers in Pediatrics, 2020)
Cerebral palsy (CP) is the most common cause of disability in childhood. Respiratory illness is the most common cause of mortality, morbidity, and poor quality of life in the most severely affected children. Respiratory illness is caused by multiple and combined factors. This review describes these factors and discusses assessments and treatments. Oropharyngeal dysphagia causes pulmonary aspiration of food, drink and saliva. Speech pathology assessments evaluate safety and adequacy of nutritional intake. Management is holistic and may include dental care, and interventions to improve nutritional intake and ease and efficiency of feeding. Behavioral, medical, and surgical approaches to drooling aim to reduce salivary aspiration. Gastrointestinal dysfunction, leading to aspiration from reflux, should be assessed objectively, and may be managed by lifestyle changes, medications, or surgical interventions. The motor disorder that defines cerebral palsy may impair fitness, breathing mechanics, effective coughing, and cause scoliosis in individuals with severe impairments; therefore, interventions should maximize physical, musculoskeletal functions. Airway clearance techniques help to clear secretions. Upper airway obstruction may be treated with medications and/or surgery. Malnutrition leads to poor general health and susceptibility to infection, and improved nutritional intake may improve not only respiratory health but also constipation, gastroesophageal reflux, and participation in activities. There is some evidence that children with CP carry pathogenic bacteria. Prophylactic antibiotics may be considered for children with recurrent exacerbations. Uncontrolled seizures place children with CP at risk of respiratory illness by increasing their risk of salivary aspiration; therefore optimal control of epilepsy may reduce respiratory illness. Respiratory illnesses in children with CP are sometimes diagnosed as asthma; a short trial of asthma medications may be considered, but should be discontinued if ineffective. Overall, management of respiratory illness in children with CP is complex and needs well-coordinated multidisciplinary teams who communicate clearly with families. Regular immunizations, including annual influenza vaccination, should be encouraged, as well as good oral hygiene. Treatments should aim to improve quality of life for children and families and reduce burden of care for carers.